Astrategy for energy efficiency using energy management techniques and renewable energy technolgies and the identification of opportunities for energy reduction at Zamorano - Escuela Agrícola Panamericana, Zamorano. (Escuela Agricola Panamericana, 2014, 2014)
Part one of this report outlines a 4-year plan for the management of energy at Zamorano, and the implementation of renewable energy and energy management training into Zamorano’s academic courses. This documents details very specifically the activities required to achieve an energy reduction of 30% in 3-10% steps. The plan includes a: plan for, and the details of renewable energy courses as well as the preliminary design of 4 on-campus solar systems. References to training programs and sample course outlines for Zamorano students and operating plant personnel training are detailed.